Quantifying the contribution of citizen science to broad‐scale ecological databases. Issue 1 (4th November 2019) - Poisson, Autumn C; McCullough, Ian M; Cheruvelil, Kendra S; Elliott, Kevin C; Latimore, Jo A; Soranno, Patricia A
Abstract : Ecological research increasingly relies on broad‐scale databases containing information collected by personnel from a variety of sources, including government agencies, universities, and citizen‐science programs. However, the contribution of citizen‐science programs to these databases is not well known. We analyzed one such database to quantify the contribution of citizen science to lake water‐quality data from seven US states. Citizen‐science programs not only provided over half of the observations for commonly sampled water‐quality measures (water clarity, nutrients, and algal biomass) from the past 31 years, but also contributed to the majority of long‐term monitoring (>15 years) for selected measures in lakes. While previous studies have demonstrated the usefulness of citizen science for research, management, policy, and public engagement, our study demonstrates that citizen science can also make valuable contributions to populating broad‐scale ecological databases. Strengthening partnerships between citizen‐science programs and monitoring agencies can help maintain and expand spatial and temporal data coverage during the "big data" era of ecology.